2017
DOI: 10.1016/j.bpj.2016.11.1994
|View full text |Cite
|
Sign up to set email alerts
|

Folding Heterogeneity in HIV-1 Frameshifting Hairpin

Abstract: draw the T2 RNA back, the re-folded RNA must be unfolded prior to returning. Importantly, the detected unfolding time (stability marker) can clearly report the identity of each folding state, from the free chain to the hairpin, and to the final pseudoknot. The time-dependent occurrence probabilities of all the folding states help us to map the entire stepwise folding pathway in the time scale from 1 second to several minutes. This RNA single-molecule folding approach would lead to broad applications in detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although frameshifting has been extensively studied in vitro and in bulk assays (Caliskan et al, 2014;Charbonneau et al, 2012;Chen et al, 2014;Lopinski et al, 2000;Mouzakis et al, 2013;Ritchie et al, 2017), the process has never been observed at the single-molecule level in living cells. This leaves many basic questions about frameshifting unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Although frameshifting has been extensively studied in vitro and in bulk assays (Caliskan et al, 2014;Charbonneau et al, 2012;Chen et al, 2014;Lopinski et al, 2000;Mouzakis et al, 2013;Ritchie et al, 2017), the process has never been observed at the single-molecule level in living cells. This leaves many basic questions about frameshifting unresolved.…”
Section: Introductionmentioning
confidence: 99%